Pengaruh Performance Expectancy, Perceived Ease of Use, dan Perceived Risk terhadap Continuance Intention pada Pengguna E-Wallet di Universitas Budi Luhur - Dwi Fani Anggraini; Yugi Setyarko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine and analyze the influence of performance expectancy, perceived ease of use, and perceived risk on continuance intention among e-wallet users at Budi Luhur University. The background to this research is based on the increasing use of e-wallets among students, which has prompted the need to understand the factors influencing the continued use of this technology. The independent variables in this study are performance expectancy, perceived ease of use, and perceived risk, while the dependent variable is continuance intention. The research method used is quantitative with a descriptive approach. The study population included all e-wallet users at Budi Luhur University. Sampling was conducted using a non-probability purposive sampling technique, which considers specific respondent criteria, resulting in 98 respondents. The sample size was determined using the Lemeshow formula. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis to examine the effect of each independent variable on the dependent variable. The results of the study show that performance expectancy has a positive and significant influence on continuance intention, indicating that the higher users' expectations of e-wallet performance, the greater their intention to continue using it. Perceived ease of use was also shown to have a positive and significant influence on continuance intention, indicating that perceived ease of use is a key factor in continued e-wallet use. Conversely, perceived risk did not have a significant influence on continuance intention, indicating that perceived risk is not a major inhibiting factor in students' decisions to continue using e-wallets.